The Effect of Color Type and Light Intensity of Light Emitting Diode (LED) Light Traps on the Types and Number of Pest Insect Catches in Rice Plantations - Iqbal Erdiansyah; Moch. Syarief; Moch. Irfan Kusairi (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2021)
The purpose of this study was to examine the effect of the type of color and light intensity of the light emitting diode (LED) Light traps on the type and number of insect pests in rice plantations. The research was conducted from November 2017 to March 2018, in Kencong Village, Jember Regency. The data collection method used Scan sampling, for 11 weeks, one week interval, starting at 07.00 p.m. to 04.00.a.m. The number of plots was 4 pieces, each 100 m2. The distance between the plots is 100 meters. Light traps in each plot, red, yellow, blue and white. Each color consists of 4 light intensities, namely 3 watts, 5 watts, 7 watts and 9 watts. Observation parameters: types and number of insect pests catches. The different types and numbers of insect pests caught were using the Kruskal-Wallis test. The normality of the data used the Shapiro-Wilt test. Statistical significance p < 0.05. Correlation between lamp color and light intensity, using the Spearman correlation test. Data were analyzed using SPSS version 23.0. The conclusions of the study were: The types of insect pests at various colors and intensity of LED light traps showed similarities, consisting of 5 orders, 6 families and 6 species. The red LED trap light indicates the highest number of pest catches. The number of insect pest catches of red LED was 475 individuals. A light intensity of 9 Watts indicates the highest number of insect pest catcheswere 568 individuals. The spearman correlation coefficient between the type of LED color and the light intensity (r) = - 0.415.